EFA6B regulates a stop signal for collective invasion in breast cancer - Racha Fayad (Nature Portfolio, 2021)
Reduced expression of EFA6B is found in highly metastatic breast cancer subtypes. Here, the authors report that loss of EFA6B promotes collective invasion through activation of the epithelial-to-mesenchymal transition program and CDC42-dependent signalling pathways in breast cancer.